A Comparison of Conservative and Operative Management of Thumb Ulnar Collateral Ligament Avulsion Fractures in Children. (November 2020) - Huynh, Minh N. Q.; Tang, Ken; Cheung, Kevin
Background: The optimal management of pediatric thumb ulnar collateral ligament (UCL) avulsion fractures remains poorly defined. The purpose of this study was to elucidate patient outcomes based on initial management and fracture characteristics.Methods: A retrospective study of all patients younger than 18 years of age presenting with a thumb UCL avulsion fracture was performed. Patients were grouped by their initial management. The primary outcome of the study was time to return to full activity. Fractures were characterized by articular surface involvement, displacement, and rotation.Results: Forty-seven patients with thumb UCL avulsion fractures were identified. Ten patients underwent surgery as initial treatment; all healed without complication, with a mean recovery time of 6.2 ± 1.8 weeks. Thirty-seven patients were treated conservatively; although most healed, the recovery time was longer (9.2 ± 8.3 weeks, adjusted hazard ratio = 2.3, 95% confidence interval = 1.0-5.5). Four cases (11%) required conversion to surgery that all healed without complications. Fractures treated with immobilization alone were significantly smaller, less displaced, and less rotated than those initially treated with surgery; however, 19 fractures that would have met criteria for surgery were treated with immobilization and successfully healed within 7.1 ± 2.9 weeks. Fracture characteristics did not predict which patients would fail conservative treatment or have prolonged recovery times.Conclusions: While surgery provided definitive treatment without delay in recovery, immobilization may not be an unreasonable treatment choice even for patients with large or displaced fractures. In cases where patients failed immobilization, surgery as a second-line treatment had good results.